2013
DOI: 10.1038/tp.2013.100
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk factors in two Utah pedigrees at high risk for suicide

Abstract: We have used unique population-based data resources to identify 22 high-risk extended pedigrees that show clustering of suicide over twice that expected from demographically adjusted incidence rates. In this initial study of genetic risk factors, we focused on two high-risk pedigrees. In the first of these (pedigree 12), 10/19 (53%) of the related suicides were female, and the average age at death was 30.95. In the second (pedigree 5), 7/51 (14%) of the suicides were female and the average age at death was 36.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 69 publications
3
53
0
Order By: Relevance
“…Consistent with this idea, the RNAseq experiment shows that PDE11A KO mice exhibit a significant reduction relative to PDE11A WT and HT mice in insulin-like growth factor binding protein 3 (IGFBP3), elevated expression of which is associated with chronic loneliness in humans (Cole et al, 2007). Although some questions remain, data presented here strongly argue that PDE11A is a key regulator of social interactions, which is consistent with the fact that PDE11A has been genetically and/or functionally associated with clinical phenotypes related to changes in social function, including major depressive disorder (Wong et al, 2006; Couzin, 2008; Cabanero et al, 2009; Luo et al, 2009; Kelsoe, 2010; Coon et al, 2013), suicide risk (an inactivating mutation, (Coon et al, 2013)), and lithium responsivity (Couzin, 2008; Kelsoe, 2010; Mertens et al, 2015; Pathak et al, in press). …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Consistent with this idea, the RNAseq experiment shows that PDE11A KO mice exhibit a significant reduction relative to PDE11A WT and HT mice in insulin-like growth factor binding protein 3 (IGFBP3), elevated expression of which is associated with chronic loneliness in humans (Cole et al, 2007). Although some questions remain, data presented here strongly argue that PDE11A is a key regulator of social interactions, which is consistent with the fact that PDE11A has been genetically and/or functionally associated with clinical phenotypes related to changes in social function, including major depressive disorder (Wong et al, 2006; Couzin, 2008; Cabanero et al, 2009; Luo et al, 2009; Kelsoe, 2010; Coon et al, 2013), suicide risk (an inactivating mutation, (Coon et al, 2013)), and lithium responsivity (Couzin, 2008; Kelsoe, 2010; Mertens et al, 2015; Pathak et al, in press). …”
Section: Discussionsupporting
confidence: 82%
“…1A) (Kelly et al, 2010, 2014; Kelly, 2014, 2015; Hegde et al, 2016; Pathak et al, in press) and little to no expression in peripheral organs (c.f., (Kelly, 2015)). PDE11A has been genetically and/or functionally associated with clinical phenotypes related to changes in social function, including major depressive disorder (Wong et al, 2006; Cabanero et al, 2009; Luo et al, 2009), suicide risk (an inactivating mutation, (Coon et al, 2013)), and lithium responsivity (Couzin, 2008; Kelsoe, 2010; Mertens et al, 2015; Pathak et al, in press). Previously, we showed that reducing PDE11A expression was sufficient to reduce social approach behavior towards a novel mouse in adult male mice, but not female mice (Kelly et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although pVAAST is primarily designed for sequence data, it is also applicable to exome chip genotyping data. pVAAST was recently used to identify candidate genes associated with an increased risk of suicide from exome chip data in extended high-risk pedigrees 28 .…”
Section: Discussionmentioning
confidence: 99%
“…table 3) which have been associated with the development of suicide [for reviews, see Turecki et al, 2012;Coon et al, 2013;Mandelli and Seretti, 2013;Sadkowski et al, 2013]. Fifteen (10%) of these 145 genes have been replicated in independent studies ( table 2 ); BDNF , HTR1A , HTR1B , SLC6A4 (5-HTTLPR) , SSAT (SAT1) , TPH1 , and TPH2 even showed association in multiple studies.…”
Section: Literature Searchmentioning
confidence: 94%